THU0702-HPR PATIENT UNDERSTANDING OF RISKS OF METHOTREXATE AND ANTI-TNF THERAPY: A CROSS-SECTIONAL STUDY . (June 2019) - Jackson, Lauren; Murray, Natalie; Plummer, Zoe; Marshall, Robert; Ndosi, Mwidimi
Abstract : Background: Disease-modifying anti-rheumatic drugs (DMARDs) have revolutionised the management and long-term prognosis of rheumatoid arthritis (RA). 1 Side-effects of DMARDs include, but are not limited to: immunosuppression, gastro-intestinal upset, skin reactions and headaches. Despite the significant potential side-effects of DMARDs, there have been limited attempts to evaluate patient understanding of the side-effects of methotrexate (MTX) 2, 3 and to our knowledge no studies with regards to anti-tumour necrosis factor (anti-TNF) therapy. Objectives: To evaluate the extent to which each of the known side-effects of MTX and anti-TNF therapy can be identified by patients receiving single or combination therapy for RA. Methods: This was a cross-sectional study conducted in a rheumatology centre in the West of England. Patients with RA, seen in the outpatient clinic within the previous 18 months were invited to participate. Participants had to belong to one of the following treatment groups: (i) MTX only (ii) anti-TNF only or (ii) combined treatment with MTX and an anti-TNF. A postal questionnaire designed by the research team was used to obtain the data. Each participant was asked to (a) select side-effects they considered to be possible from their treatment, (b) tick if they had experienced this side-effect, and (c) select whether they believed this side-effect to be common or not. Descriptive analyses were used to determine the proportion (percentage) of patients who correctly identified the possible side-effects, correctly identified them as common, and had experienced them. Summary results are presented as ranges (minimum to maximum) and their corresponding percentages. Results: Of the 300 patients invited, 119 returned a completed questionnaire; 48 (40%) on MTX only, 25 (21%) on anti-TNF only and 46 (39%) on combined MTX and anti-TNF. Their mean (SD) age was 62.5 (12.8) years, disease duration 13.5 (12.4) years, 111 (93%) had completed compulsory education and 94 (79%) were female. Most participants (115, 97%) spoke English as their first language. Correct identification of each possible side-effect ranged from 29% to 63% of participants in the MTX only group, 15% to 41% of participants in the anti-TNF only group and 18% to 62% of participants in the combined MTX and anti-TNF group. Correctly recognising these as common ranged from 13% to 52% of participants in the MTX only group, 4% to 35% of participants in the anti-TNF only group and 8% to 64% of participants in the combined MTX and anti-TNF group. Of those correctly identifying possible side effects, 22% to 55% of participants in the MTX only group, 1% to 25% of participants in the anti-TNF only group and 8% to 56% of participants in the combined MTX and anti-TNF group reported experiencing them. Conclusion: Our data suggests that a considerable number of patients are unable to correctly identify the most common side-effects of DMARDs used in RA management. Effective patient education and involvement in treatment decision-making will allow patients to be more aware of potentially serious side-effects of DMARDs. References: [1] Cicirello, S, et al. Improving treatment with methotrexate in rheumatoid arthritis - development of a multimedia patient education program and the MiRAK, a new instrument to evaluate methotrexate related knowledge. Semin Arthritis Rheum. 2014; 43:437-46. [2] Fayet, F, et al. The development of a questionnaire to evaluate rheumatoid arthritis patient's knowledge about methotrexate. J Clin Nurs. 2015; 25:682-689. [3] Barton, J, et al. Poor knowledge of methotrexate associated with older age and limited English language proficiency in a diverse rheumatoid arthritis cohort. Arthritis Res Ther. 2013; 15:157. Disclosure of Interests: None declared